Mapping of SARS-CoV-2 IgM and IgG in gingival crevicular fluid: Antibody dynamics and linkage to severity of COVID-19 in hospital inpatients. Issue 2 (August 2022) - Ijaz, Samreen; Dicks, Steve; Jegatheesan, Keerthana; Parker, Eleanor; Katsanovskaja, Ksenia; Vink, Elen; McClure, Myra O.; Shute, J.; Hope, Joshua; Cook, Nicola; Cherepanov, Peter; Turtle, Lance; et al.
Highlights: Gingival crevicular fluid forms a useful analyte for detecting SARS-CoV-2 antibody. There are differential patterns of antibody reactivity across NP and Spike. Higher antibody levels in early acute phase linked to severity of COVID-19.